Efeito do exercício aeróbio sobre a pressão arterial e variabilidade cardiovascular em jovens normotensos filhos de pais hipertensos com privação parcial do sono: um ensaio clínico randomizado - Souza, Larissa Isabelle Soares de (2019)
Background: Risk factors such as heredity and lifestyle contribute to the onset of hypertension and the development of cardiovascular disease. Associated with the genetic burden, sleep deprivation (SD), which has been commonly experienced by society today, can promote dysregulation in the cardiovascular control system. On the other hand, physical exercise can beneficially modulate hemodynamic parameters and cardiovascular autonomic control. Objective: To evaluate the effect of partial sleep deprivation and aerobic exercise on blood pressure (BP) and cardiovascular variability in normotensive young children of hypertensive parents. Methods: Randomized clinical trial that evaluated 20 normotensive young children of hypertensive parents, of both sexes, with a mean age of 24.6 ± 3.3 years and a mean BMI of 23.8 ± 2 kg/m2, which were allocated to the usual sleep group and the sleep deprivation group. All volunteers participated in a moderate intensity aerobic exercise session and a control session (without exercise). SD was performed using 50% of each participant's usual sleep time. Data were tabulated in Excel and SPSS (Statistical Package for Social Sciences, IBM®) version 20.0 for Windows. The effect size was calculated to evaluate the magnitude of intrasessional differences (post vs pre) and between sessions (post vs post). Logarithmic transformation was employed in the absolute components of high frequency (HF) and low frequency (LF) heart rate banking. Results: BP decreased over 24 hours after the exercise session, which is more expressive when the subject performs the exercise after a regular night's sleep compared to a partially private night's sleep: SBP -5mmHg (d=0.57) vs -1mmHg (d=0.16) and DBP -5mmHg (d=1.08) vs -4mmHg (d=0.6). When compared to the control session, it was observed that exercise promoted greater BP reduction at all post-intervention moments, in the private sleep group, with an average effect size in SBP60min (d=0.44), strong in DBP60min (d=0.94) and mean in DBPWake (d=0.51). Conclusion: Partial sleep deprivation leads to increased BP in normotensive young children of hypertensive parents, and physical exercise is able to minimize such hemodynamic disorders.